The Results of Unstable Intertrochanteric Femur Fracture Treated with Proximal Femoral Nail Antirotation-2 with respect to Different Greater Trochanteric Entry Points - Sharan Mallya; Surendra U. Kamath; Rajendra Annappa; Nithin Elliot Nazareth; Krithika Kamath; Pragya Tyagi (Advances in Orthopedics)
Background. Proximal femoral nail antirotation-2 (PFNA-2) has been widely used to treat intertrochanteric fractures with varied outcomes in the previous studies. The entry point of the nail plays an important role in achieving acceptable reduction, stable fixation, and avoiding implant related complications. This study was proposed to determine the optimal greater trochanteric entry point for PFNA-2 in unstable intertrochanteric femur fractures. Methods. We conducted an observational study on 40 patients with unstable intertrochanteric fracture treated with PFNA-2 implant in a tertiary care hospital. The patients were grouped into two based on the entry point: group L for lateral and group M for medial entry. Randomization was carried out by assigning the patients to the group by alternate allocation. The quality of reduction, tip apex distance, Cleveland index, and all the complications were noted. The final follow-up was conducted at six months. The functional outcome was evaluated using modified Harris hip score. The data analysis was performed using Student’s t-test, chi square test, and Mann–Whitney test. A P value below 0.05 was considered significant. Results. Forty patients with 20 patients treated with medial entry point were included in group M and 20 patients in group L with lateral entry point. The group L had an average tip apex distance of 20.53 and group M had 20.02 (P=0.8). The complication of screw back out was seen in 3 out of 4 patients with poor reduction in group L. As per the Cleveland index, 6 patients in each group had suboptimal position and 4 out of 6 patients in group L with suboptimal position had screw back out. The lateral cortex impingement was seen in 14 patients of group L and 6 patients in group M with significant comparison (P=0.01). Three patients in group L had varus collapse with screw back out. Also, none in group M (0.05). The average modified Harris hip score in group L at six months follow-up was 71.94 and 76.8 in group M (P=0.84). Conclusion. Overall, to achieve good quality of fixation and reducing damage to gluteus medius entry point for PFNA-2 should be 5 mm medial to the greater trochanter tip.